Secularisation in Australian Education Since 1910 - Carden, Clarissa (Brill Research Perspectives in Humanities and Social Sciences Ser., 2021)
Intro -- Contents -- Tables -- Abstract -- Keywords -- Part 1: Secularisation and Australian Education: Definitions and Approaches -- Introduction -- The Plan of This Book -- Part 2: Religious Instruction and State Schools: Expansion and Constraint in the Early Twentieth Century -- Introduction -- "Free, Secular, and Compulsory" Education in Australian History -- Case Study 1: Shared Christianity and the Introduction of Religious Instruction to Queensland State Schools -- Case Study 2: German Schools and the Limits of Shared Christianity -- Conclusion -- Part 3: Government and Non-government Schools: Questions of Faith, Choice, and Control in the 1960s and 1970s -- Introduction -- Public Funding and Christian Schools -- Social Science and Humanities Education and the Christian Right -- Case Study 3: The Introduction of Federal Funding for Religious Schools -- Case Study 4: Banning macos and semp: A Local Victory for the Religious Right -- Conclusion -- Part 4: Twenty-First Century Debates: Christian Influence in a Complex System -- Introduction -- Secular Systems? Religion in Contemporary Australian Education -- Case Study 5: Challenges to School Chaplaincy -- Case Study 6: Simultaneous Fights in Queensland -- Conclusion -- Part 5: Conclusion -- Acknowledgements -- _Hlk78908199.